Divercities understanding super-diversity in deprived and mixed neighbourhoods - Oosterlynck, Stijn ca. 20./21. Jh; Verschraegen, Gert 1973-; Kempen, Ronald van 1958-2016 (Policy Press, 2019)
Provides a comparative international perspective on superdiversity in cities, with explicit attention given to social inequality and social exclusion on a neighbourhood level